Translation and validation of Pediatric Quality of Life Inventory™ 3.0 Diabetes Module (PedsQL™ 3.0 Diabetes Module) in Brazil-Portuguese language - Leila F. dos S. Garcia; Thais Della Manna; Caroline de Gouveia Buff Passone; Lygia Spassapan de Oliveira (Elsevier, 2018)
Objective: The aim of the present study was to create a translated version of the Pediatric Quality of Life Inventory™ 3.0 Diabetes Module (PedsQL™ 3.0 Diabetes Module) in Brazilian Portuguese that was conceptually equivalent to the original American English version and to linguistically validate it in a Brazilian pediatric population with type 1 diabetes mellitus and their parents or caregivers. Methods: The instrument was translated, back-translated, and then administered to 83 children/adolescents (5-18 years) with type 1 diabetes mellitus and their family members and to 25 parents/caregivers of patients aged between 2 and 4 years. The final translated version was tested for reliability by analyzing internal consistency, intraobserver (test-retest) reliability, and concurrent validity. Results: Cronbach's alpha coefficient for the total score of the questionnaires of children/adolescents (α = 0.85) and their parents (α = 0.82) was above the recommended minimum of 0.70 for group comparisons. Intraobserver reliability and concurrent validity exhibited a significant positive correlation (p < 0.001), indicating the reliability of the translated instrument. A moderate but significant positive correlation (r = 0.40; p < 0.001) was demonstrated between the total scores of patient self-report and parent proxy-report scales. There was no significant correlation between glycated hemoglobin (HbA1c) levels and the respective scores in the questionnaires answered by patients and their parents/caregivers. Conclusion: The analysis of the translated version of the PedsQL™ 3.0 Diabetes Module revealed adequate psychometric characteristics with respect to reliability and validity following administration to a sample of Brazilian children/adolescents with type 1 diabetes mellitus and their caregivers. Resumo: Objetivo: Produzir uma versão do questionário Pediatric Quality of Life Inventory™ 3.0 Diabetes Module (PedsQL™ 3.0 Diabetes Module) para a língua portuguesa do Brasil, que fosse conceitualmente equivalente à versão original em inglês, e proceder à sua validação linguística numa população pediátrica brasileira portadora de diabetes melitus tipo 1 (DM1) e seus pais ou cuidadores. Métodos: A tradução do instrumento foi feita pela metodologia de tradução-tradução reversa, foi aplicado a 83 crianças/adolescentes (5-18 anos) portadores de diabetes mellitus tipo 1 com seus parentes e a 25 pais/cuidadores de pacientes entre 2 e 4 anos de idade. A confiabilidade da versão traduzida foi avaliada pelas seguintes análises: consistência interna, confiabilidade teste-reteste e validade concorrente. Resultados: O coeficiente alfa de Cronbach para a pontuação total do questionário das crianças/adolescentes (α = 0,85) e seus pais (α = 0,82) excedeu o mínimo recomendado 0,70 para comparação entre grupos. Na confiabilidade intraobservador e validade concorrente observou-se correlação positiva e estatisticamente significativa (p < 0,001), indicou indicando a fidedignidade do instrumento traduzido. Na comparação entre os escores totais obtidos por pais/cuidadores e crianças/adolescentes, houve uma correlação positiva, pequena, mas significativa (r = 0,40; p < 0,001). Não houve correlações estatisticamente significativas entre os níveis de hemoglobina glicada e os escores obtidos nos questionários respondidos pelos pacientes e seus pais/cuidadores. Conclusão: As análises do instrumento PedsQL™ 3.0 Módulo Diabetes demonstraram propriedades psicométricas adequadas em termos de confiabilidade e validade quando aplicado nessa amostra de crianças/adolescentes brasileiros portadores de DM tipo 1 e seus cuidadores. Keywords: Validation studies, Quality of life, Type 1 diabetes mellitus, Child, Adolescent, Palavras-chave: Estudos de validação, Qualidade de vida, Diabetes mellitus tipo 1, Criança, Adolescente